Optimalisasi Dana Zakat Untuk Mengatasi Masalah Kemiskinan di Indonesia - Hamran, Rachmat Ghafur; Sudirman, Sudirman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this research is to unravel how zakat can be a solution to solve the problem of poverty in Indonesia. In this study, a qualitative approach is used with library research. The result of this article is that the potential of zakat is a solution to answer the problem of poverty in Indonesia, due to the large number of Islamic populations. The role of zakat in alleviating poverty is wealth redistribution, economic empowerment, access to health and education, assistance for vulnerable groups, overcoming humanitarian crises, and improving living standards.